Review Article about Study of Irritable Bowel Syndrome - Zahraa Rashad Abdulwahid; Israa basim abdulzahra; Bader Ayad Hadi; Muhanad Jabbar Hassan (American Journal of Biology and Natural Sciences, 2024)
Despite years of advising patients to change their diet and take fiber supplements, the evidence surrounding the use of fiber for the treatment of functional bowel diseases is limited. However, irritable bowel syndrome (IBS) is the most common functional gastrointestinal disorder worldwide and is associated with numerous social and economic costs. Health-related quality of life is often impaired in IBS patients. The pathophysiological mechanisms underlying IBS remain poorly defined. The therapeutic approach for IBS patients is symptom-based, and fiber may play an important role in treatment. Among the different types of fiber, water-soluble, non-clumping fiber appears to be a promising option for the treatment of IBS. Partially hydrolyzed guar gum (PHGG) is a water-soluble, non-clumping fiber that has shown therapeutic benefits. The co-occurrence of IBS and common mental disorders such as anxiety and depression is well known. A range of biological and psychosocial disease mechanisms are common to both disorders, many of which contribute to dysfunction of the gut-brain axis. Clinical psychiatric illnesses and comorbid psychological disorders add to the functional impairment and disease burden of individuals with IBS. In clinical trials, guar gum reduced symptoms in constipation- and diarrhea-predominant forms of IBS and reduced abdominal pain. Furthermore, an improvement in quality of life was observed in IBS patients during and after treatment with partially hydrolyzed guar gum. Furthermore, PHGG appears to have probiotic properties as it increases the colonic contents of short-chain fatty acids, lactobacilli, and bifidobacteria.